PENGARUH PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) PROVINSI DAERAH ISTIMEWA YOGYAKARTA (2013-2017) - Mintarsih, Ratna Ambar; Lampunu, Rukmana Is (PRIMA EKONOMIKA, 2020)
ABSTRACTThe purpose of this study was to measure the effect of regional taxes andlocal user fees on increasing local own-source revenue in the province ofYogyakarta Special Region in the 2013-2017 period. The data used in this study aresecondary data obtained from the official website of the Central Statistics Agencyin the form of the APBD report of the Special Region of Yogyakarta. The populationand sample in this study are all districts and cities in the Yogyakarta Special Regionprovince. Data analysis techniques used in this study were descriptive statisticalanalysis, multiple regression analysis, and hypothesis testing consisting of t test, Ftest and determination test (R2) as well as calculation of effective contributions,which were tested using SPSS 2.3.Based on testing the hypothesis by using the t test, it was concluded thatlocal taxes affect the increase in regional own-source revenue and local user feesdo not affect the increase in regional original income. Based on the results of the Ftest of regional taxes and regional levies together affect the increase in localrevenue. determination (R2) is known that the adjusted R square result is 0.910 or91.0%, this shows that local original income can be explained by the local taxvariable and regional retribution of 91.0%. As for the results of the calculation ofeffective contributions, it is known that the contribution of local taxes by 89.19% tothe increase in local revenue while for the regional levies the contribution of theeffect on the increase in the local revenue is only 2.61%.Keywords: Regional Tax, Regional Retribution, and Local Original Revenue(PAD).